A identificação do mosquito como agente da transmissão da febre amarela e o reflexo nas ações determinadas pelo serviço sanitário do estado de São Paulo no início do Século XX - Ortiz, Carlos Eduardo (2016)
Yellow fever a disease before limited only the region of the coast after in São Paulo and after 1889 leaves the city of Santos and reaches regions of the inside of the State of São Paulo, becoming for doctorsand authorities a still bigger problem, for not restricted to the sick person, but also causing problems of social and economic order. The epidemics of the disease had taken immigration restrictions, affecting the trade of the regions and starting a panicof local populations where it revealed. In this thesis official documents were studied and medical publications, with the objective to identify the epidemics of yellow fever that had reached São Paulo close to the turn of century 19th for the 20th , theactions taken for its containment as well as in that were based such actions. Recommended actions for its containment initially were based on the hygiene presuppositions and had remained up to 1901. With settlement of the function of mosquito in the transmission of disease, the Sanitary Service of São Paulo, under direction of Emilio Marcondes Ribas, centers around its actions in the extermination of insect as form to tackle yellow fever, as explained further Sanitary Instructions published in 1903. This research allowed to verify as Emilio Ribas is going to constitute base of sanitary measures that had contained yellow fever in São Paulo